Private University Performance: Leadership Commitment, Intellectual Capital, Collaborative Capability, and Competitive Advantag - Irsan Aras; Iskandar A.A; Defrizal Defrizal; Andala Rama Putra Barusman; Afrizal Nilwan (Penerbit Goodwood, 2026)
Purpose: This study explains how leadership commitment and intellectual capital are converted into private university performance through collaborative capability and competitive advantage. Research Methodology: A quantitative, explanatory, cross-sectional survey was conducted among private higher education institutions supervised by LLDikti Region II in Southern Sumatra, Indonesia. Proportionate stratified random sampling selected 39 institutions from a population of 160. Data from 395 leaders and managerial personnel were collected using five-point Likert scales and analyzed with structural equation modeling in LISREL 8.80. Results: The model explained 80% of the variance in collaborative capability, 84% in competitive advantage, and 88% in institutional performance. Leadership commitment did not significantly predict collaborative capability or competitive advantage, although it had a positive direct effect on performance. Intellectual capital significantly predicted all three outcomes. Collaborative capability strengthened competitive advantage but had no significant direct effect on performance, while competitive advantage was the strongest predictor of performance. Conclusions: Strategic resources generate institutional outcomes when they are organized into stakeholder-valued advantages. Limitations: The cross-sectional, single-source design and regional setting limit causal and broader generalization. Contributions: The study extends resource-based and dynamic-capability reasoning by identifying collaborative capability as a resource-conversion mechanism and offers practical priorities for capability building in private higher education.